Controlling antimicrobial resistance in dentistry with innovative technologies and sustainable solutions - Aftab Ahmed Khan; Mohammed Abdullah Alhadi; Ahmed Abdullah Alhadi (Universitas Airlangga, 2026)
Background: Antimicrobial resistance (AMR) is a significant global health threat, with dentistry contributing substantially through antibiotic misuse. Purpose: This review examines the distinct mechanisms of resistance in oral microorganisms, including biofilm formation and enzymatic degradation of antibiotics, which complicate treatment and contribute to persistent infections. Reviews: Clinical challenges encompass endodontics, periodontics, and oral surgery, which are exacerbated by inconsistent antibiotic management in dental practice. Targeted strategies like phage therapy and CRISPR-Cas, and by using advanced tools and therapeutic strategies such as quorum-sensing inhibitors, nanozyme and catalytic antibacterial systems, photodynamic therapy, RNA-based antimicrobials and magnetic or electric-responsive systems, disintegration of mature biofilms and enhanced drug penetration are possible. Conclusion: Integrating these innovations can advance sustainable antimicrobial strategies, reducing resistance spread and ensuring effective oral healthcare for future generations.